Dua Kota Satu Atap: Kebijakan Pemukiman Penduduk Kota Jakarta dan Depok (1970-an Hingga Akhir 1990-an) - saring saring (Sosio e-Kons, 2019)
Jakarta as the center of administrative and governmental activities, as well as the center of national economic activities, finally made this city a prima donna for urbanites to come and try their luck in Jakarta. The shadow of success and hope for improving economic conditions from the area of origin becomes a kind of hope that always lives in the minds of the urbanites. In reality, the presence of urban people has become a new problem faced by the Special Capital Region of Jakarta, the presence of urbanites who generally do not have decent skills, and provision of administration (as citizens) is a problem that is quite significant for the development of the city of Jakarta. The existence of urbanites who always come and increase in number on the one hand, and on the other hand the existence of space for residential areas in the increasingly depleted city of Jakarta, making the issue of the needs of the trustees and decent housing is quite difficult to obtain. In order to overcome the problem of fulfilling residential needs for the people of Jakarta, the DKI Jakarta government, through the power possessed by the central government, made Depok city an alternative area to divide the heavy burden of Jakarta in terms of population issues (residential settlements).